Features of the strength abilities of the world's leading armwrestlers weighing 80-100 kg - Bezkorovainyi, Dmytro; Kamayev, Oleg; Mishyn, Maksym; Vlasko, Stanislav; Plotnytskyi, Leonid; Glyadya, Sergey; Kliuka, Andrii (Харківський національний педагогічний університет імені Г. С. Сковороди, 2024)
Purpose: determination of the main components of power capabilities that ensure the success of the competitive exercise of armwrestlers weighing 80-100 kg. Material and Methods. The study involved 4 best armwrestlers in the world weighing from 80 to 100 kg (m = 87.50 ± 2.47 kg) in 2017–2020: athlete 1 is a multiple world champion weighing 90 kg (Ukraine), athlete 2 is a multiple champion world champion weighing 82 kg (Ukraine), athlete 3 - multiple world champion weighing 93 kg (Ukraine), athlete 4 - multiple winner of international competitions weighing 85 kg (USA). During the study, strength indicators were determined in 4 competitive exercises. Strength indices in all test exercises were measured in a static mode by an FB5k series electrical tenzodynamometer (Poland) with an accuracy class of up to 100 g, which was mounted on a special armwrestling table using a specially made block device. The created design was called the “ARM1 Device” (patent 43082). During the statistical analysis, the following parameters were calculated: maximum and relative strength, total strength index in four strength exercises (F), time to reach maximum strength (t), speed-strength index (F/t), average strength index of four exercises (F/4), gradient of the total strength of four exercises (t0,5F), strength index in the first 100 ms and 500 ms, speed-strength index in the first 500 ms (F500/t500), hour of reaching a force of 1 kg (t0,5F/(0,5×F); Pearson correlation analysis. Results. As a result of the study, the main data on the speed-strength indicators of armwrestlers were obtained and analyzed. In the process of testing, according to the indicators of time periods and given efforts of dynamic strength, the features of the manifestation of the explosive, fast and slow strength of arm wrestlers 80-100 kg were established. Conclusions. The study made it possible to establish indicators of the speed -strength index, strength gradient, the ability to manifest dynamic strength in the first 500 ms, clearly characterizing the speed -strength capabilities of armwrestlers and allowing to determine the features and nature of the manifestation of their dynamic strength. This makes it possible to determine the natural ability to manifest dynamic strength, as well as to select and predict the performance of promising athletes, to specify the direction and content of the training process, and to clarify the program of participation in competitions.

Мета: визначення основних складових силових можливостей, що забезпечують успішність змагальній вправі армрестлерів вагою 80-100 кг. Матеріал і методи. У дослідженні взяли участь 4 кращих армрестлера світу вагою від 80 до 100 кг (m = 87,50 ± 2,47 кг) у 2017–2020 роках: спортсмен 1 – багаторазовий чемпіон світу вагою 90 кг (Україна), спортсмен 2 – багаторазовий чемпіон світу вагою 82 кг (Україна), спортсмен 3 – багаторазовий чемпіон світу вагою 93 кг (Україна), спортсмен 4 – багаторазовий призер міжнародних змагань вагою 85 кг (США). Визначено чотири силові тестові вправи, що забезпечують виконання змагальної дії в армрестлінгу: згинання пальців, розгинання молотком, гак і згинання кисті. Ці вправи виконувалися лівою і правою руками. Силові показники у всіх тестових вправах вимірювали електротензодинамометром серії FB5k (Польща) з класом точності до 100 г, закріпленим на спеціалізованому столі для армрестлінгу за допомогою спеціально виготовленого блокового приладу – «Прилад ARM1» (патент №43082). У ході статистичного аналізу були розраховані наступні параметри: максимальна та відносна сила, сумарний індекс сили в чотирьох силових вправах (F), час досягнення максимальної сили (t), швидкісно-силовий індекс (F/t), середня сила. індекс чотирьох вправ (F/4), градієнт загальної сили чотирьох вправ (t0,5F), індекс сили в перші 100 мс і 500 мс, швидкісно-силовий індекс в перші 500 мс (F500 / t500), час досягнення сили 1 кг (t0,5F / (0,5×F)); кореляційний аналіз Пірсона. Результати. За результатами дослідження отримано та проаналізовано основні дані швидкісно-силових показників армрестлерів. В процесі тестування за показниками часових відрізків і даними зусиль динамічної сили встановлено особливості прояву вибухової, швидкої і повільної сили армрестлерів вагою 80-100 кг. Висновки. Проведене дослідження дало змогу встановити показники швидкісно-силового індексу, градієнту сили, здібність прояву динамічної сили за перші 500 мс, яки чітко характеризують швидкісно-силові можливості армрестлерів і дозволяють визначити особливості та характер прояву їхньої динамічної сили. Це дає змогу визначити природну здібність прояву динамічної сили, а також зробити відбір і прогнозування результативності найперспективніших спортсменів, конкретизувати спрямованість і зміст тренувального процесу й уточнити програму участі у змаганнях.
Особливості прояву силових здібностей провідних армрестлерів світу вагою 80-100 кг
Keywords: armsport; armwrestling; armwrestlers; dynamic strength; strength indicators; армспорт; армрестлінг; армрестлери; динамічна сила; силові показники